Polymorphism in the EREG gene confers susceptibility to tuberculosis - Wen Cao; Liu-lin Luo; Wei-wei Chen; Li Liang; Ran-ran Zhang; Yan-lin Zhao; Jin Chen; Jun Yue (BMC Medical Genetics, 2019)
Abstract Background Host genetic factors affect the immune response to Mycobacterium tuberculosis (Mtb) infection as well as the progression of the disease. Epiregulin (EREG) belongs to the epidermal growth factor (EGF) family, which binds to the epidermal growth factor receptor (EGFR) to regulate the immune response of the host during infections. Our study aimed to compare EREG levels in tuberculosis (TB) patients and healthy controls and assess whether polymorphisms in EREG increase the risk of TB. Methods We used ELISA to determine the plasma EREG level from 30 healthy controls and 50 tuberculosis patients. By evaluating the EREG gene from 624 TB patients and 600 healthy controls, we determined the allelic and genotypic frequencies for association with susceptibility to TB infections in this group. Results This paper shows that the pulmonary tuberculosis (PTB) and extrapulmonary tuberculosis (EPTB) groups showed a significantly higher plasma EREG level (1014 ± 733.9 pg/ml, 700.2 ± 676.6 pg/ml, respectively) than the healthy controls (277 ± 105.4 pg/ml). The rs2367707 polymorphism was associated with a higher risk of PTB and EPTB (P = 0.00051, P = 0.0012). Analyses of haplotype frequencies found that people with the haplotype CACAT had a higher risk of PTB and EPTB (P = 0.00031, OR = 1.43; P = 0.000053, OR = 1.65). Moreover, the rs6446993 polymorphism of the EREG gene was found to be associated with EPTB (P = 0.00087, OR = 1.54; 95% CI = 1.23–1.94). Conclusions Compared to that of healthy controls, the level of EREG in the plasma of TB patients increased significantly. Based on these data, we demonstrated that EREG polymorphisms are genetic factors for susceptibility to TB and various forms of TB.